KEPAHAMAN DAN KESIAPAN MAHASISWA ATAS PENGGUNAAN TEKNOLOGI INFORMASI DALAM SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS INFORMASI AKUNTANSI DENGAN ETIKA SEBAGAI MODERATING VARIABLE - Ahmad Hafidh Agustin; Merlyana Dwinda Yanthi (Universitas Boyolali, 2021)
This study aims to obtain empirical evidence regarding students' perceptions of their understanding and readiness as users of information technology in accounting information systems on information quality. Also, the following research was conducted to obtain empirical evidence of the influence of ethical aspects in the use of information technology on information quality. Purposive sampling was chosen as a method of collecting data from the respondents of undergraduate accounting students. Of the total population, 75 respondents were sampled. Data were analyzed using SPSS statistical analysis with descriptive test technique, multicollinearity test, heteroscedasticity test, classical assumption test, and absolute difference value test. The result is that the understanding and readiness of information technology users in the accounting information system affects the quality of accounting information and user ethics becomes a moderating variable that strengthens this influence.